2009
DOI: 10.2527/jas.2008-1222
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of insulin-like growth factor-I-induced changes in messenger ribonucleic acid expression in cultured porcine granulosa cells: Possible role of insulin-like growth factor-I in angiogenesis1,2

Abstract: Insulin-like growth factor-I in conjunction with gonadotropins are important stimulators of mitosis and ovarian steroid production by granulosa and thecal cells, which are required for normal oocyte development and hormonal feedback signaling to the hypothalamus and pituitary. However, a comprehensive evaluation of the changes in gene expression induced by IGF-I has not been conducted. Our objective was to characterize granulosa cell gene expression in response to IGF-I treatment. Porcine granulosa cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…As TSP-1 is known to be a potent inhibitor of angiogenesis (reviewed in [24]), the studies presented here provide further evidence for the pro-angiogenic influence of IGF-1 in the ovary and suggest that a reduction in TSP-1 expression occurs to allow a rapid shift towards a pro-angiogenesic environment at a key stage in the developing follicle. Very recent studies in the porcine follicle demonstrate that IGF-1 significantly suppresses TSP-1 mRNA expression in granulosa cells, strongly supporting the results described here [8]. These studies extend the mRNA findings by demonstrating a mechanism behind the rapid decay and confirming that the change in mRNA level is rapidly mirrored in the expression of TSP-1 protein.…”
supporting
confidence: 79%
See 4 more Smart Citations
“…As TSP-1 is known to be a potent inhibitor of angiogenesis (reviewed in [24]), the studies presented here provide further evidence for the pro-angiogenic influence of IGF-1 in the ovary and suggest that a reduction in TSP-1 expression occurs to allow a rapid shift towards a pro-angiogenesic environment at a key stage in the developing follicle. Very recent studies in the porcine follicle demonstrate that IGF-1 significantly suppresses TSP-1 mRNA expression in granulosa cells, strongly supporting the results described here [8]. These studies extend the mRNA findings by demonstrating a mechanism behind the rapid decay and confirming that the change in mRNA level is rapidly mirrored in the expression of TSP-1 protein.…”
supporting
confidence: 79%
“…In very recent studies with primary cultures of porcine granulosa cells, it has been demonstrated that multiple mRNA species are positively and negatively regulated by IGF-1, further supporting the potential importance of this growth factor in granulosa cell function [8]. Among the genes suppressed by IGF-1 is thrombospondin-1 (TSP-1) [8].Thrombospondin-1 (TSP-1), a homotrimeric glycoprotein that participates in a wide range of biological processes, including cell proliferation, differentiation, cell adhesion, angiogenesis, cell-cell and cell-matrix interactions [9][10][11]. We have previously demonstrated that the expression of TSP-1 and TSP-2 during the bovine ovarian cycle is gonadotrophin-dependent and have identified distinct patterns of TSP-1 expression corresponding to different follicular stages [12].…”
mentioning
confidence: 87%
See 3 more Smart Citations